ART, TRAINING AND TRANSFORMATION IN THE TRAJECTORY OF THREE CONTEMPORARY BRAZILIAN ARTISTS - Johas, Regina; Menna Barreto, Menna Barreto; Kunsch, Graziela; Tremonte, Fábio (Farol, 2021)
Art, academic training and transformation are the escape lines of the interviews with three contemporary Brazilian artists: Jorge Menna Barreto, Graziela Kunsch and Fábio Tremonte. Jorge Menna Barreto’s work draws possibilities for us to answer this question. Placing itself on the boundaries between art and life, his projects, intertwined with a strong educational vocation, deal with poetic and artistic thinking based on the notions of diversity and forestry. The formative and transforming character of art is also decisive to the artist, activist, teacher and researcher Graziela Kunsch. Her production is closely related to political and social contexts and allows us to reflect on the possibilities of bringing changes to society, since it promotes questions capable of inciting social transformations.Fábio Tremonte talks about his artistic propositions and a “do-together” in times of pandemic. Starting from his previous experience at Escola da Floresta, in which he proposes an ecology of knowledge as a counterpoint to the epistemological domain coming from the north, the artist explains his new projects.